2019
DOI: 10.1016/j.ebiom.2019.06.035
|View full text |Cite
|
Sign up to set email alerts
|

A subunit of V-ATPases, ATP6V1B2, underlies the pathology of intellectual disability

Abstract: Background Dominant deafness-onychodystrophy (DDOD) syndrome is a rare disorder mainly characterized by severe deafness, onychodystrophy and brachydactyly. We previously identified c.1516C > T (p.Arg506X) in ATP6V1B2 as cause of DDOD syndrome, accounting for all cases of this genetic disorder. Clinical follow-up of DDOD syndrome patients with cochlear implantation revealed the language rehabilitation was unsatisfactory although the implanted cochlea worked well, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 65 publications
2
26
0
Order By: Relevance
“…ATP6V1B2 is ubiquitously expressed in the brain [50] and is related to synaptic transmission [51]. Atp6v1b2 knock-in mice show cognitive defects in passive avoidance and novel object recognition tests [52] and the ATP6V1B2 rs1106634 A allele is a risk factor in hippocampal cognitive deficits [53]. HSC70 is upregulated in Alzheimer's disease brains [54].…”
Section: Discussionmentioning
confidence: 99%
“…ATP6V1B2 is ubiquitously expressed in the brain [50] and is related to synaptic transmission [51]. Atp6v1b2 knock-in mice show cognitive defects in passive avoidance and novel object recognition tests [52] and the ATP6V1B2 rs1106634 A allele is a risk factor in hippocampal cognitive deficits [53]. HSC70 is upregulated in Alzheimer's disease brains [54].…”
Section: Discussionmentioning
confidence: 99%
“…Using a zebrafish model replicating this mutation, it was shown that the V-ATPase can still assemble but that the affinity of some subunits comprising the holoenzyme is lowered. A role of the B2 subunit in other types of cognitive impairment has also been recognized ( 188 , 189 ).…”
Section: Sensory Perceptionmentioning
confidence: 99%
“…In particular, dominant deafness-onychodystrophy (DDOD) syndrome caused by de novo mutation c.1516 C > N (p.Arg506X) in ATP6V1B2 is a rare disorder with chief complaints of severe deafness, onychodystrophy, and brachydactyly (Table 1) [38]. This group's latest research [39] indicated four interesting results: (1) atp6v1b2 knockdown zebrafish had developmental defects in multiple organs and systems; (2) Atp6v1b2 c.1516 C > N knock-in mice led to cognitive disorders, based on the impaired hippocampal CA1 region from the pathology;…”
Section: Lysosomal-function-related Genes Essential For the Autophagymentioning
confidence: 99%
“…In particular, dominant deafness-onychodystrophy (DDOD) syndrome caused by de novo mutation c.1516 C > N (p.Arg506X) in ATP6V1B2 is a rare disorder with chief complaints of severe deafness, onychodystrophy, and brachydactyly ( Table 1 ) [ 38 ]. This group’s latest research [ 39 ] indicated four interesting results: (1) atp6v1b2 knockdown zebrafish had developmental defects in multiple organs and systems; (2) Atp6v1b2 c.1516 C > N knock-in mice led to cognitive disorders, based on the impaired hippocampal CA1 region from the pathology; (3) the normal hearing thresholds of Atp6v1b2 c.1516 C > N in 24-week-old knock-in mice, suggested that a compensation mechanism exists in the auditory system; and (4) V-ATPases assembly still occurred in Atp6v1b2 c.1516 C > N. However, the interaction between the E and B2 subunits was weaker than in the wild type (WT). They confirmed that the defectiveness of Atp6v1b2 leads to CNS impairments and extends the phenotype range of DDOD syndrome.…”
Section: Autophagy- and Lysosomal-function-related Genes And Hearimentioning
confidence: 99%